Complexities and Context of Scaling Up: A Qualitative Study of Stakeholder Perspectives of Scaling Physical Activity and Nutrition Interventions in Australia - Koorts, Harriet; Maple, Jaimie-Lee; Eakin, Elizabeth; Lawrence, Mark; Salmon, Jo (Frontiers in Public Health, 2022)
Abstract Background: Scaling up population health interventions is a context-orientated, dynamic and multi-stakeholder process; understanding its influences is essential to enhance future scaling efforts. Using physical activity and nutrition interventions in Australia as case examples, the aim of this paper is to identify core influences involved in scaling up physical activity and nutrition interventions, and how these may differ by context and stakeholder. Methods: A qualitative study involving semi-structured telephone interviews with individuals representing academic, government and non-government organisations with involvement in scaling up state and national physical activity and nutrition interventions. Interview questions were derived from the WHO report ‘20 Questions for Developing a Scaling up Case Study’, and mapped against four key principles and five core areas in the WHO ExpandNet framework for scaling up: 1) The innovation; 2) User organisation; 3) Environment; 4) Resource team and; 5) Scale up strategy. Data were analysed thematically. Results: Nineteen interviews were conducted (government=3; non-government=5; and academic=11 sectors) involving eight scaled up interventions, targeting nutrition (n=2), physical activity (n=1) or a combination (n=5). Most themes aligned to the ‘Environment’, including: (i) political (e.g., personal agendas); (ii) social (e.g., lack of urgency); and (iii) sector/workforce (e.g., scale up accountability) factors. Themes relating to ‘Scale up strategy’ (e.g., flexibility and evaluation transparency) were next most commonly occurring. Whilst themes were broadly consistent across participants, government participants had a more policy-oriented perspective on the scale up process. Academics discussed a tension between the generation and use of evidence, and the influence of political climates/interest on scale up decisions. Conclusions: Attributes of the ‘Environment’ and ‘Scale up strategy’ consistently featured as major influences on successful outcomes, while the role of evidence differed greatly between participant groups. A multisector scale up strategy for future interventions may enable the complexities of environmental and political contexts to be incorporated into scale up planning. Keywords: Scale up, scaling, physical activity, nutrition, intervention, stakeholder, population health